MENINGKATAN MUTU PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SMKN 1 CIKAMPEK TAHUN PELAJARAN 2018/2019 - MAKMUR, MAKMUR (Lembaga Kajian dan Pengembangan Profesi Pendidik Indonesia, 2021)
The success of education in educational units is strongly influenced by the role of the principal as a researcher in the learning leadership of teachers. The principal in the education unit has a strategic role in determining the success and failure of teachers in learning in which there is a learning evaluation system. the author is interested in conducting School Action Research (PTS) entitled